Dietary supplementation of vitamin D prevents the development of western diet-induced metabolic, hepatic and cardiovascular abnormalities in rats - Mazzone, Giovanna; Morisco, Carmine; Lembo, Vincenzo; D’Argenio, Giuseppe; D’Armiento, Maria; Rossi, Antonella; Giudice, Carmine Del; Trimarco, Bruno; Caporaso, Nicola; Morisco, Filomena (United European gastroenterology journal, 2018)
Background The western diet high in fat and fructose may cause metabolic disorders and cardiovascular diseases. Objective To evaluate whether long-term daily vitamin D3 supplementation prevents hepatic steatosis and cardiovascular abnormalities and restores insulin sensitivity caused by fat diet in rats without vitamin D deficiency. Methods Three groups of rats were fed for 6 months with standard diet (SD), western diet (WD) or WD containing 23 IU/day/rat vitamin D3, respectively. Tail-cuff systolic blood pressure (SBP)measurements in conscious rats and transthoracic echocardiography were performed in basal condition, and after 3 and 6 months of diet. Hepatic steatosis and myocardial fibrosis were assessed in liver and cardiac tissues using standard methods. Serum insulin and 25(OH)D3 concentrations were determined using rat-specific ELISA kits. Insulin resistance was determined according to the homeostasis model assessment of insulin resistance (HOMA-IR) method. Results Sixty-one per cent of hepatocytes in WD rats had steatotic vacuoles compared with just 27% in rats on a WD plus vitamin D3 (p < 0.05).HOMA-IR was reduced in rats with vitamin D supplementation compared with WD alone (19.4 ± 5.2 vs 41.9 ± 8.9, p < 0.05). Rat blood pressure and left ventricular mass were both reduced by vitamin D3 supplementation. Conclusion In animal models of liver and cardiovascular metabolic damage, the supplementation of vitamin D3 shows liver and cardio-protective effects.